Hypothermia revisited: Impact of ischaemic duration and between experiment variability. Issue 10 (October 2017) - Rewell, Sarah SJ; Jeffreys, Amy L; Sastra, Steven A; Cox, Susan F; Fernandez, John A; Aleksoska, Elena; van der Worp, H Bart; Churilov, Leonid; Macleod, Malcolm R; Howells, David W
To assess the true effect of novel therapies for ischaemic stroke, a positive control that can validate the experimental model and design is vital. Hypothermia may be a good candidate for such a positive control, given the convincing body of evidence from animal models of ischaemic stroke. Taking conditions under which substantial efficacy had been seen in a meta-analysis of hypothermia for focal ischaemia in animal models, we undertook three randomised and blinded studies examining the effect of hypothermia induced immediately following the onset of middle cerebral artery occlusion on infarct volume in rats (n = 15, 23, 264). Hypothermia to a depth of 33℃ and maintained for 130 min significantly reduced infarct volume compared to normothermia treatment (by 27–63%) and depended on ischaemic duration (F(3, 244) = 21.242, p < 0.05). However, the protective effect varied across experiments with differences in both the size of the infarct observed in normothermic controls and the time to reach target temperature. Our results highlight the need for sample size and power calculations to take into account variations between individual experiments requiring induction of focal ischaemia.